اثر جودة الحياة الوظيفة على سلوك المواطنة التنظيمية ــ دراسة حالة ــ - فاطمة الزهراء, بوزيد; عزيزة, كرمادي; صبرينة, هزلاوي (جامعة الوادي - University of Eloued, 2023)
"هدفت هذه الدراسة الى معرفه اثار جوده الحياه الوظيفية على سلوك المواطنة التنظيمية ولتحقيق هذا الهدف تم الاعتماد على المنهج الوصفي التحليلي في الجانب النظري من خلال جمع البيانات والمعلومات من المراجع العلمية المختلفة لوصف خصائص، وابعاد ومفاهيم الظاهرة المدروسة وتحليل العلاقات فيما بين مكوناتها المختلفة، اما في الجانب التطبيقي فقد تم الاعتماد على المنهج الوصفي التحليلي من خلال جمع المعلومات الأولية من الميدان المبحوث فيه، باستعمال استمارة الاستبيان وتم توزيعها على عمال مركز مكافحه السرطان بالوادي لتشمل العينة على 115 عاملا وتم الاعتماد بشكل نهائي على 81 عاملا، كما تم الاستعانة في تحليل نتائج اجابات الاستبيان بالأدوات الإحصائية مثل البرنامج الاحصائي spss برنامج Excel ليتم التوصل الى نتائج مختلفة اهمها ان لجوده الحياه الوظيفية اثر كبير وفعال على السلوك المواطنة التنظيمية التي يعيشها العامل رغم المستوى المتوسط لجودة الحياةالوظيفية داخل مركز مكافحه. الكلمات المفتاحية: جودة الحياة الوظيفة، المواطنة التنظيمية، سلوك المواطنة التنظيمية. " ABSTRACT: This study aimed to find out the impact of the quality of career life on the behavior of organizational citizenship, and to achieve this goal, the descriptive analytical approach was relied on in the theoretical aspect by collecting information and data from various scientific references to describe the characteristics, dimensions and concepts of the studied phenomenon, and analyzing the relationships between its various components, while in the applied side, the descriptive analytical approach was adopted by collecting preliminary information from the field researched using the questionnaire form and distributed to the workers of the Cancer Control Center. The sample included 115 workers, and 81 workers were finally relied upon, and statistical tools such as the statistical program (SPSS) and the Excel program were used to analyze the results of the questionnaire answers to reach various results, the most important of which is that the quality of life has a significant and effective impact on the organizational citizenship behavior of the worker despite the average level of quality of career life within the Cancer Control Center. Keywords: quality of life, organizational citizenship, organizational citizenship behavior.
Keywords: جودة الحياة الوظيفة، المواطنة التنظيمية، سلوك المواطنة التنظيمية.; quality of life, organizational citizenship, organizational citizenship behavior.